Strategy Implementation in Conflict Management to Prevent Violence in Transportation Education Institutions: Implementasi Strategi dalam Manajemen Konflik guna Mencegah Kekerasan di Lembaga Pendidikan Transportasi - Hartati, Diah Vitaloka; Sultan; Sabaruddin; Nurmala, Eka; Saifudin, Iksan (SABIQ: Jurnal Sosial dan Bidang Pendidikan, 2024)
Education is a fundamental basis for building national civilization. Educational institutions in the transportation sector continue to transform to enhance the quality of education. In connection with the violence in the educational environment, it is vital to carry out this study to provide an overview for the community, teaching, and education staff, and educational policymakers, especially in the transportation sector. The study was carried out using a method in the form of a literature study also called a literature review. The results of this study include: 1) Conflicts in educational institutions usually occur between individuals, groups, or between parts of the environment; 2) Conflict management in educational institutions can be conducted by mediating promptly to prevent conflicts from escalating.; and 3) Implementation of conflict management strategies can be done by creating professional code of ethics learning policies and routine activities to increase team collaboration outdoors (outbound).